Biology - Starr, Cecie (Brooks/Cole, 2006)
[In this book, the authors] weave examples of problem solving and experiments through its pages to show the power of thinking critically about the natural world. [They] highlight core concepts, current understandings, and research trends for major fields of biological inquiry. [They] explain the structure and function of a broad sampling of organisms in enough detail so students can develop a working vocabulary about life's parts and processes. [They] selectively introduce applications that may help students sense the value of learning the core concepts.-Pref